PENCIPTAAN KARYA ASSEMBLAGE ART MELALUI ELABORASI BENDA NON-SENI - Ali Rahim, Muhamad; Setiawan, Hendra; Adrian Triskanto, Leonel (Penerbit Lafadz Jaya, 2025)
The development of assemblage art works in the discourse of art in Indonesia seems to have not been widely explored by artists, craftsmen, or art academics, thus inspiring and underpinning the author to elaborate on it in research-creation. This project contains the activity of creating art works based on experiments on found objects as the main material, which is carried out in a structured design pattern and improvisation into assemblage art works. It begins with collecting various everyday objects, then be constructed and assembled into valuable art media. The goal is to develop unique-personal, 'environmentally friendly', and solution-oriented works of art. Through the use of unused objects in the environment as an alternative solution to the problem of 'saturation' of conventionality materials for art works. The method of creation is arranged in stages of exploration-experimentation-manifestation through the synergy of designed concepts and dynamic improvisation. This project produces three assemblage art works in the form of figurative visuals that combine various forms of objects. The use of non-art objects can become a trigger for unique creations because it offers alternatives, while also potentially providing insight into the productivity of creative work due to the unlimited possibilities for using materials.